2022
DOI: 10.1186/s12912-022-00916-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and use of evidence based practice (EBP) among registered nurse-midwives practicing in central hospitals in Malawi: a cross-sectional survey

Abstract: Background Even though evidence based practice (EBP) is being considered as a critical element in improving the quality of health services and achieving excellence in patient care, there is currently little knowledge of how EBP relates to nursing and midwifery in Malawi. This paper is a report of a study describing EBP knowledge, attitudes, and use of registered nurse-midwives practicing in central hospitals across Malawi. Methods The descriptive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
10
1
2
Order By: Relevance
“…Furthermore, these findings agree with a study by Zammar ( 2022 ), which concluded that most nurses are uninformed of the significance of EBP in their profession. However, these findings contradict a study by Kaseka and Mbakaya ( 2022 ), who concluded that the nurses viewed EBP positively, and their attitude towards EBP seemed more positive. However, they did not use it much because they lacked the organizational support and competence to do so.…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, these findings agree with a study by Zammar ( 2022 ), which concluded that most nurses are uninformed of the significance of EBP in their profession. However, these findings contradict a study by Kaseka and Mbakaya ( 2022 ), who concluded that the nurses viewed EBP positively, and their attitude towards EBP seemed more positive. However, they did not use it much because they lacked the organizational support and competence to do so.…”
Section: Discussioncontrasting
confidence: 94%
“…[5]. However, it became lower than other studies [14][15][16][17]. On the other hand, it became higher than research conducted in Chitwan and Nepal [18,19].…”
Section: Knowledge Of Based Practice Concerning the Positionmentioning
confidence: 63%
“…When the PICOT method was used, most of the clinical questions had errors that would impact the description of the clinical issue as a driver for the systematic search for evidence. This search could yield irrelevant evidence and waste valuable resources and time, further perpetuating a major barrier to the implementation of EBP and the cultivation of an EBP culture (Gallagher‐Ford et al., 2023; Kaseka & Mbakaya, 2022; Shayan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%